130 A decision aid for cervical cancer screening – how users perceive the information about benefits and harms. (20th August 2018) - Fechtelpeter, Dennis; Janßen, Inger; Keller, Sabine; Koch, Klaus; Lampert, Ulrike; Schürmann, Christoph; Seidl, Astrid; Wegmann, Martin; Zschorlich, Beate; Schröer-Günther, Milly
Abstract : Objectives: Germany plans to implement an organised screening programme for cervical cancer screening. This involves a change from the annual offer of a Pap test to a combined Pap/HPV test every three years for women aged 35 and older. Also, regular invitations containing a decision aid will be sent out to all women. The Institute for Quality and Efficiency in Health Care (IQWiG) was commissioned to develop the invitation letter and the decision aid, and to have them tested by users. One focus was the communication of benefits and harms. Method: A systematic search was performed to analyse the benefits and harms of cervical cancer screening. Additionally, the long-term effects were modelled based on an existing and validated decision analysis tool. The invitation letter and the decision aid were tested in qualitative focus groups (32 participants) and an online survey (2014 participants). The process also included a public commenting procedure. Results: Most users perceived the decision aid to be informative, helpful and balanced. The majority found the information on possible overtreatment to be relevant. Healthcare professionals were more reluctant to provide information on harms in the decision aid, fearing it might lead to lower participation in screening. The survey showed that the decision aid only had little impact on screening intention. Most women consider the benefits of screening to outweigh the harms. The majority would participate in the screening programme, despite the possibility of overtreatment and the potential harms of conization. Conclusions: Although cervical cancer screening can lead to a substantial reduction of cancer morbidity and mortality, possible harms should also be communicated in a decision aid. Doing so did not lead to a substantial difference in the acceptance of the screening programme.